Implementasi Inovasi Pembelajaran “Gadis Ceria” pada Mata Pelajaran Pendidikan Pancasila - Sutrisno Sutrisno; Erna Yayuk; Lud Waluyo (Universitas Negeri Malang, 2026)
This study aims to describe the implementation, supporting and inhibiting factors, and solutions to the obstacles of the